2014
DOI: 10.1179/2295333714y.0000000013
|View full text |Cite
|
Sign up to set email alerts
|

HIV disclosure in the workplace

Abstract: Objectives: As HIV is currently a chronic and manageable disease, an increasing amount of people living with HIV (PLHIV) are (again) active on the labour market. Since research on this topic is scarce, this study aimed to explore experiences of PLHIV in the workplace, especially concerning disclosure and adherence to antiretroviral therapy. Methods: A questionnaire was developed and validated in collaboration with Sensoa (Flemish expertise centre for sexual health) and participants were recruited using flyers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…The role of gender was reported in two studies. One study found no difference [22], whereas the other concluded that women were less likely than men to disclose their HIV-positive status at the workplace [24].…”
Section: 222mentioning
confidence: 98%
See 4 more Smart Citations
“…The role of gender was reported in two studies. One study found no difference [22], whereas the other concluded that women were less likely than men to disclose their HIV-positive status at the workplace [24].…”
Section: 222mentioning
confidence: 98%
“…The level of disclosure to employers/colleagues was reported in six studies and ranged from 22-50% [21][22][23][24][25][26]. In two studies a comparison was made between employers and colleagues [21]; the conclusion was that the level of disclosure to the employer is lower than that to colleagues (22-27% vs. 30-33%).…”
Section: Level Of Disclosurementioning
confidence: 99%
See 3 more Smart Citations